Genetic and phenotypic parameters estimated from single and multi-trait restricted maximum likelihood procedure - RAHEJA, K L; VINAYAK, A K; KALRA, SUNIL (The Indian Journal of Animal Sciences, 2013)
Restricted maximum likelihood method was used to obtain variance and covariance components among 6 traits, viz. age and weight at first calving, first lactation milk yield, first lactation length, first calving interval and profit up to first lactation using single and multi-trait model (2-, 3-, 4-, 5- and 6-trait). Data consisted of first lactation records on 1 463 Murrah buffaloes sired by 65 Murrah bulls spread over 28 years (1966-88), and maintained at 4 military dairy farms at Ambala, Ferozpur, Lucknow and Meerut. Same model was used in single and multi-trait procedures which contained year-season of calving and farm as fixed effects, and sires within farm as random effect. Estimates of genetic and phenotypic Correlations obtained from single and multi-trait analyses were different. Parameter estimates varied depending upon the type of analysis (single- or multi-trait model) and the traits included in the multi-trait analysis. The 6-trait model analysis through canonical transformation was more efficient in terms of computer time than single trait analyses of same 6 traits. Results suggested that choice of parameter estimation method for a breeding scheme should be based on goals of improvement. In sire evaluation programmes, traits included in multi-trait analysis should correspond to the traits of interest in the breeding goals.